2018
DOI: 10.1111/cen.13724
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of maternal thyroid function with foetal brain development: Epidemiological interpretation and overview of available evidence

Abstract: Thyroid hormone is an important regulator of early brain development, particularly during early stages of gestation during which foetal thyroid hormone availability depends on the maternal transfer of thyroid hormones. There is a wide range of experimental studies showing that low maternal thyroid hormone availability is associated with suboptimal brain development parameters. While few clinical studies have shown that overt maternal hypothyroidism is associated with lower child IQ, the question whether more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 93 publications
(184 reference statements)
0
22
0
2
Order By: Relevance
“…Moreover, a large cohort study recently showed that both mild hypo‐ and hyperthyroidism in the first trimester of prenatal brain development altered grey/white matter ratios in the progeny, suggesting that lineage specification was altered in embryonic development . Other neurological disorders including attention‐deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and schizophrenia, characterized by abnormal neuronal numbers and networks, are also suspected to have a developmental aetiology of which suboptimal TH levels might be one of the underlying causes . Lastly, a histological analysis of the brain of an MCT8‐deficient foetus showed loss of some neuronal subtypes, and a hypomyelinated state, suggesting similar problems in NSC biology and specification caused by insufficient TH uptake during early development .…”
Section: Evidence For Thyroid Hormone Regulating Embryonic Nsc Physiomentioning
confidence: 99%
“…Moreover, a large cohort study recently showed that both mild hypo‐ and hyperthyroidism in the first trimester of prenatal brain development altered grey/white matter ratios in the progeny, suggesting that lineage specification was altered in embryonic development . Other neurological disorders including attention‐deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and schizophrenia, characterized by abnormal neuronal numbers and networks, are also suspected to have a developmental aetiology of which suboptimal TH levels might be one of the underlying causes . Lastly, a histological analysis of the brain of an MCT8‐deficient foetus showed loss of some neuronal subtypes, and a hypomyelinated state, suggesting similar problems in NSC biology and specification caused by insufficient TH uptake during early development .…”
Section: Evidence For Thyroid Hormone Regulating Embryonic Nsc Physiomentioning
confidence: 99%
“…Meta-analysis of three studies shows that maternal SCH has a negative effect on subsequent intelligence score in the offspring, but these data are uncorrected for parental educational level and economic status 23. Practically, all studies that demonstrate a positive association between thyroid function and child neurodevelopment find the association between maternal T4 levels rather than TSH 24. This is consistent with known gestational physiology as it is T4, not TSH, which crosses the placental barrier and is required for neuronal migration in the fetus.…”
Section: Does Sch During Pregnancy Cause Harm?mentioning
confidence: 98%
“…This stability is vital for the developing brain (Ahmed, 2011;Ahmed et al, 2010;Aszalós, 2007;Coccini et al, 2007). Normal levels of THs regulate the neurogenesis process during development (Bernal, 2017;Fanibunda, Desouza, Kapoor, Vaidya, & Vaidya, 2018;Korevaar, Tiemeier, & Peeters, 2018;Moog et al, 2017;Richard & Flamant, 2018). Alternatively, THs can control the monoaminergic system via their receptors on the NE, E and DA-ergic fibers (Aszalós, 2007).…”
Section: T a B L E 4 Maternal Administration Ofmentioning
confidence: 99%